2008
DOI: 10.1063/1.2909587
|View full text |Cite
|
Sign up to set email alerts
|

Onset of shear layer instability in flow past a cylinder

Abstract: Global stability analysis of the flow past a cylinder is carried out to determine the critical Re for the onset of shear layer instability. To suppress the wake mode that leads to von Kármán vortex shedding, flow past one-half of the cylinder is studied. The linearized perturbation equations for an incompressible flow are written in a moving frame of reference that travels with the perturbation and solved using a stabilized finite element method. The critical Re for the onset of convective instability is found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
1
5
1
Order By: Relevance
“…This is in contrast to the trend reported by Shair et al (1963) and Coutanceau & Bouard (1977). In more recent work, Mittal et al (2008) imposed centreline symmetry and studied the onset of shear-layer instability in the flow past a cylinder. They find that the separated shear layer loses stability at low Reynolds numbers with very small growth rates.…”
Section: Introductioncontrasting
confidence: 78%
See 2 more Smart Citations
“…This is in contrast to the trend reported by Shair et al (1963) and Coutanceau & Bouard (1977). In more recent work, Mittal et al (2008) imposed centreline symmetry and studied the onset of shear-layer instability in the flow past a cylinder. They find that the separated shear layer loses stability at low Reynolds numbers with very small growth rates.…”
Section: Introductioncontrasting
confidence: 78%
“…Whilst this may be true in certain contexts, and there are many counter-examples, it is our view that without a detailed and accurate study, one cannot immediately draw such conclusions about the flow in the current context. Careful numerical studies, such as byMittal et al (2008), who investigated the onset of shear layer instability in the flow past a cylinder, show good agreement between simulations and global frequencies predicted. InAbdessemed et al (2009), the computational domain extends to a lateral extent of 12.5 cylinder diameters, and streamwise extent of approximately 100 cylinder diameters and Dirchlet conditions are imposed on the boundaries for the perturbations.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…The onset of shear layer instability has been studied extensively in the past. Mittal et al (2008) showed, via global convective analysis of the flow past half a cylinder, that the shear layer attached to the cylinder becomes unstable at Re¼54. Bloor (1964) reported that the onset of shear layer instability takes place at Re $ 1300.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the shear layer instability can be excited in a certain range of frequencies and at Re as low as 100. In a very recent study Mittal, Kottaram & Kumar (2008) showed that the origin of these kind of instabilities can be traced down to very low values of Re. However, at these low Re this convective instability has a very low growth rate compared to that of the regular Kármán shedding and, therefore, it cannot be observed in the experiments.…”
Section: Introductionmentioning
confidence: 99%